PERANCANGAN GAME PLATFORMER PEMBURU KOIN MENGGUNAKAN GODOT ENGINE - Ferdi; Arnomo, Sasa (LPPM Universitas Putera Batam, 2022)
Video game applications as software require a development process. The research objective is to build and design a platformer type video game using Godot Engine. The supporting software used in the development of video games in this study uses the Godot Engine. The results of the research entitled Coin Hunter, where players control a character named blanc to collect coins scattered in a remote forest. Design and development can use Godot Engine as a tool from other game engines. The design process includes the use of assets and programming on the Godot Engine game engine. Godot Engine was chosen for the reason that it is not subject to royalty fees. Assets can be created using free and open-source applications so that the design does not require exorbitant application purchases.